Etnomatematika Pada Pola Batik Gumelem Melalui Analisis Geometri Transformasi - dianlestari; Kusno, Kusno (Pendidikan Matematika Universitas PGRI Yogyakarta, 2024)
Gumelem batik is batik made by the people of Gumelem Village, Susukan District, Banjarnegara Regency, One of the typical Gumelem batik producers who still maintains the traditional method making batik is the “Wardah” batik house owned by Mr. Budi Triono. The typical motifs of this batik are the sekar jagad motif, the udan liris motif, the arjuna temple motif, and the dawet ayu banjarnegara motif. Batik cloth culture has been recognized as an intangible world heritage, but its benefits are limited to the cloth. It is still rare for people to use batik culture as a mathematics learning medium. Mathematics that combines cultural concepts with mathematical elements is called ethnomathematics. In this research, typical Gumelem batik motifs will be discussed mathematically using the concept of geometric transformation. The method used descriptive-qualitative, with an ethnographic approach. The result of the research is that, for several typical Gumelem motifs analyzed, it turns out that all of three motifs contain mathematical elements, namely geometric transformation. This research is aimed at developing mathematics teaching materials based on the culture of Gumelem village. Keywords: Ethnomathematics, Batik Gumelem, Geometric Transformation